School Learning from the Seeding Project in the Context of Child Care - Holguin-Alvarez, Jhon (2021)
The research proposed to develop scientific learning and research skills, developing in the pre-experimental method. We executed a seeding program with cognitive and cultural exchange in 250 individuals from a Children's Assistance Complex. In this sample, urban schoolchildren (without knowledge of the use of natural resources) and of Andean origin (with knowledge of sowing and harvesting) participated. The experiment was based on the application of four didactic phases: (1) intercultural organization, (2) collaboration for analysis, (3) experimentation, (4) scientific argumentation. We found an increase in scientific learning in the sample and their abilities to formulate problems, formulate hypotheses, argue and formulate results. The proficiency and cognitive interrelation allowed this improvement, being the main contribution of the study to the science area.